2015
DOI: 10.3945/ajcn.114.093294
|View full text |Cite
|
Sign up to set email alerts
|

Community-based management of severe acute malnutrition in India: new evidence from Bihar

Abstract: Background: An estimated one-third of the world’s children who are wasted live in India. In Bihar state, of children <5 y old, 27.1% are wasted and 8.3% have severe acute malnutrition (SAM). In 2009, Médecins Sans Frontières (MSF) initiated a community-based management of acute malnutrition (CMAM) program for children aged 6–59 mo with SAM.Objective: In this report, we describe the characteristics and outcomes of 8274 children treated between February 2009 and September 2011.Design: Between February 2009 and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
75
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 20 publications
15
75
2
Order By: Relevance
“…The present study also found that higher mortality rate than reports from Tigray [10], Southern region of Ethiopia [18] and India [15]. However, it is lower than reports from Uganda [12], Sudan [13], Jimma University Specialized Hospital [16], Woldiya General Hospital [17] and Rural Ethiopia [19].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The present study also found that higher mortality rate than reports from Tigray [10], Southern region of Ethiopia [18] and India [15]. However, it is lower than reports from Uganda [12], Sudan [13], Jimma University Specialized Hospital [16], Woldiya General Hospital [17] and Rural Ethiopia [19].…”
Section: Discussionsupporting
confidence: 68%
“…Not only recovery and death rate but also the other outcome indicators in this study showed that there were in the minimum standard set of sphere project values/international standards [9]. The recovery rate in our study is higher than previous findings from Tigray [10], Kamba District [11], Uganda [12], Sudan [13], Tamale Teaching Hospital [14] and India [15]. But it is lower than findings from Jimma University Specialized Hospital [16], Woldiya General Hospital [17], Southern region of Ethiopia [18] and Rural Ethiopia [19].…”
Section: Discussioncontrasting
confidence: 55%
“…Children managed at specialized units located at health facilities also require follow up services at their households after discharge in order to maintain a continuum of care and support and to prevent relapse [19,20]. The eastern Indian state of Bihar has generated encouraging results through community based intervention in this regard [21]. The current investigation, by highlighting a severe state of under-nutrition in Sundarbans, thus underscores the need for establishing outreach activities paired with facility based intervention.…”
Section: Discussionmentioning
confidence: 90%
“…This has also been postulated more recently by academics theoretically, arguing that India suffers a kind of malnutrition that is somewhat peculiar, being 'acute-on-chronic' rather than purely 'acute' (9). Not only does this have implications for the understanding of its determinants, it also seems to have an effect on relative mortalities and morbidities, as seen in two rigorous studies of large-scale CMAM interventions in India of the primarily medical typology (1,10). While resulting in lower mortalities, it also makes recovery more difficult and far lower recovery rates are seen as compared to Africa with similar interventions (11).…”
Section: The Justificationmentioning
confidence: 96%